Analysis of lard’s aroma by an electronic nose for rapid Halal authentication. - Mokhtar, Nurjuliana; Che Man, Yaakob; Mat Hashim , Dzulkifly (Springer-Verlag, 2011)
An electronic nose was successfully used to detect and discriminate lard from other types of animal body fats and samples containing lard. The results are presented in the form of VaporPrint™, the image of the polar plot of the odor amplitudes from the surface acoustic wave (SAW) detector frequency. In the VaporPrint™, the radial angles representing the sensor provides individual fingerprints of the aroma of different animal body fats. Principal component analysis (PCA) was used to interpret the data and it provided a good grouping of samples, with 61% of the variation accounted for by PC 1 and 29% accounted for by PC 2. All of the lard-containing samples formed a separate group from the samples that were free from lard. This method can be developed into a rapid method for detecting the presence of lard in food samples for Halal authentication.